A szerbiai parlamenti választások eredményei - Kovács, Teréz (Tér és Társadalom, 1991)
Out of the six republics of Jugoslavia, the first free, multi-party parliamentary elections after the Second World War were held in Serbia and Crna Gora on December 9, 1990. In the other Jugoslav republics, elections had taken place earlier, and the winners were the national parties in all the republics. At the presidential elections, which was also direct, either a „better" communist of the socialist regime (e.g.: K. Grigorov, former Jugoslav foreign minister), or a reform communist (M. Kucan), or a slandered communist (Tudjman) won. At the same time, the party that became socialist from communist ended up only at the second, or even the third place. Election results were different in Serbia and Crna Gora than in the other republics. In this study, the author deals with Serbia. Crna Gora is the smallest republic of Jugoslavia (with a little bit more than half a million inhabitants); there two republics are the closest to Serbs, and their election results were also similar. In Serbia, there were 250 constituencies, and in the first round, the winner had to gain 1 plus 50 % of votes, if minimum 50 % of the voters in the republic voted at the elections. The president of republic, and 38 % of the representatives were elected already in the first round. The second round of elections was held on December 23. At this time, in the remaining 154 constituencies, the citizens voted on one of the two nominees who reached the best result in the first round. In the second round, the winner was the person who gained more votes, independent from the number of voters. In the first round, 71.5 % , while in the second round, 48.3 % of the 7 million registered voters voted. This result is the outcome of the fact that at Kosovo, less than 10% of the Albanians voted, who – at the same time – give 85 % of the population. They do not consider the system legitimate, because the Serb rule terminated the parliament, and outlawed the Albanian press. In the first round, the Serbian Socialist Party gained 87 places, while the strongest oppositional party – Serb Movement for Renewal – none. After this, the parties that were against the socialists called for coalition, because they realized, that otherwise they could not form a government. Thus the only aim was to have more parties among the future opposition. After the second round, the election results were the following: Serbian Socialist Party 194; Serb Movement for Renewal 19, Democratic Union of Hungarians in Voivodina 8, Democratic Party 7, and 22 more places were obtained by one of the remaining parties. The opposition reached good results in Voivodina, Belgrade and the second largest city of Serbia, Kragujevac. The Democratic Union of Hungarians in Voivodina undertook the role of representing the Hungarians in Jugoslavia. In Northern Bacska, where the majority of inhabitants is Hungarian, their representatives won. According to the preliminary data of 1991 census, 340 thousa nd Hungarians live in Serbia. There were 32 nominees for presidency, and Slobodan Milosevics got 65.3 % of votes, Vuk Draskovics 65.3% , and Ivan Duric got 5.5 %. Milosevics, the former party leader won, because two years earlier he terminated the federations of Voivodina and Kosovo, and successfully sup- •ressed especially the Albanians. Sorry to say, but this nationalism is characteristic not only of the socialist party, but also of the biggest oppositional party. Both parties are the same in this respect.